Pengaruh Suhu dan Waktu Pengeringan terhadap Aktivitas Antioksidan Teh Herbal Celup Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Kholifah, Ariani Nisfin; Mayun Permana, I Dewa Gde; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
This research aimed to determine the effect of temperature and drying time on antioxidant activity of starfruit leaf herbal tea bags and to obtain the best drying temperature and time that can produce starfruit leaf herbal tea with the best antioxidant activity. This research was conducted by using experimental design with Complete Randomized Design factorial pattern of two factors which are drying temperature (50oC, 60oC, 70oC) and drying time (120 minutes, 180 minutes, 240 minutes). There were 9 treatment combinations, each treatment combination was repeated 2 times so that the number of treatment combinations was 18 experimental units. The data obtained were analyzed by analysis of variance. If the treatment had a significant effect, it would be followed by the Duncan Multiple Range Test. The results showed that interaction beetwen drying temperature and time treatment had a very significant effect on antioxidant activity, total phenol, total flavonoids, water content of starfruit leaf herbal tea, and bitter flavor, and had no significant effect) on color, aroma, taste and overall acceptance. The drying temperature of 50oC with a drying time of 120 minutes was the best temperature and drying time to produce herbal tea bags of starfruit leaves with an antioxidant activity of 87.8049% and based on the IC50 value of 10595.95 ppm, water content of 9.53%, the total phenol content was 1.38 mg GAE / g, the total flavonoid level was 0.94 mg QE / g, and sensory properties of color (liked), aroma (slight liked), flavor (slight bitter, slight liked) and overall acceptance (slightly liked).